A systematic review of the clinimetric properties of measures of habitual physical activity in primary school aged children with cerebral palsy - Mitchell, L.; Ziviani, J.; Oftedal, S.; Boyd, Roslyn (2013)
Regular participation in physical activity is an important determinant of health for children and adolescents with cerebral palsy (CP). However, there is little consensus on the most valid or reliable method to measure physical activity in this population. This study aimed to systematically review the psychometric properties of habitual physical activity (HPA) measures in primary school-aged children with CP. Databases were systematically searched for measures assessing physical activity over more than one day and had evidence of validity, reliability and/or clinical utility in children aged 6-12 years with CP. Ten measures met inclusion criteria and their quality was assessed in twelve studies. Quality of the included studies was appraised using the consensus-based standards for the selection of health measurement instruments (COSMIN) checklist. Measures were moderately to strongly correlated to criterion measures, with study quality rated as Fair (+) to Poor (0). Only four measures had evidence of reliability. Accelerometers provide a valid measure of HPA with good clinical utility; however they do not have documented reliability in this population. No one measure appears ideal to record HPA in primary school-age children with CP and further research is necessary to determine the psychometric properties of HPA measurement instruments in this population.